Durable ultra‐low‐platinum ionomer‐free anode catalyst for hydrogen proton exchange membrane fuel cell. (20th February 2020) - Ostroverkh, Anna; Dubau, Martin; Kúš, Peter; Haviar, Stanislav; Václavů, Michal; Šmíd, Břetislav; Fiala, Roman; Yakovlev, Yurii; Ostroverkh, Yevhenii; Johánek, Viktor
Summary: An ultra‐low‐platinum catalyst based on finely dispersed platinum (Pt) deposited on a highly porous complex microporous layer was investigated as a candidate of durable anode catalyst for hydrogen oxidation reaction (HOR) in proton exchange membrane fuel cells. Etching of teflonated and nitridized base carbon substrate in oxygen plasma and simultaneous deposition of cerium oxide were applied to increase active surface area and electrochemical activity of the platinum nanocatalyst. Ultra‐low loadings of Pt (between 0.85 and 8.5 μg cm −2 ) deposited by magnetron sputtering on this substrate were assembled with Nafion 212 membrane and commercially available Pt/C cathodes (300‐400 μg cm −2 Pt). Such membrane electrode assembly (MEA) with extremely low Pt content at anode can deliver high output power densities, reaching 0.95 W cm −2 or 0.65 W cm −2 with only 1.7 μg cm −2 of Pt, using H2 as fuel and pure O2 or air as an oxidant, respectively. Although electrocatalysts with highly dispersed active metals are known to often suffer from irreversible degradation, the above MEAs proved to be very stable when the cell was subjected to a durability test under heavy duty conditions of on/off cycling. The system with lower Pt content is more prone to water flooding which can, however, be eliminated by maintaining better control over the fuel humidity. Average decay of the cell voltage less than 50 μV h −1 was obtained in the cycling regime, while excellent stability <10 μV h −1 is achievable under the static load of 0.4 A cm −2 . Abstract : Ionomer‐free Pt/ceria/CNx ‐based catalyst containing extremely low amounts of platinum proved to be very durable for HOR in low‐temperature proton exchange membrane fuel cells. This novel nanostructured material, prepared by magnetron sputtering, allows reduction of Pt load down to μg cm −2 range without compromising fuel cell performance in terms of both power density and durability.